Network security JumpStart - Strebe, Matthew (SYBEX, 2002)
Build Your Network Security Career on a Solid Foundation. Whether you're setting out to earn a security certification or just want to know more about the security issues faced by all network administrators, Network Security JumpStart is the place to begin.